2012
DOI: 10.1590/s1984-70332012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to anthracnose stalk rot (Colletotrichum graminicola) in tropical maize inbred lines

Abstract: -Generation means was used to study the mode of inheritance of resistance to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…The coefficients of variation for the three experiments were of low magnitude, with range of 6.26 to 15.96% (Table 2). These values are considered suitable for field trials involving the pathogen x host interaction, and are close to those obtained by other researchers in the same pathosystem (Coêlho et al 2001, Rezende et al 2004, Matiello et al 2012.…”
Section: Resultssupporting
confidence: 85%
“…The coefficients of variation for the three experiments were of low magnitude, with range of 6.26 to 15.96% (Table 2). These values are considered suitable for field trials involving the pathogen x host interaction, and are close to those obtained by other researchers in the same pathosystem (Coêlho et al 2001, Rezende et al 2004, Matiello et al 2012.…”
Section: Resultssupporting
confidence: 85%
“…This could be due to ILB-4726, ILB-938, BPL-710 and Gebelcho (its pedigree comprises ILB-4726) which are genetically close inbred lines. Matiello et al (2012) and Lim and White (1978) reported similar results of estimates of heterosis for maize anthracnose disease and Colletotrichum graminicola resistance in maize, respectively. Path analysis helps in measuring the direct effect of each trait as well as its indirect effect through other characters contributing to yield.…”
Section: Discussionmentioning
confidence: 52%
“…(2014), there are different races, pathotypes, and haplotypes of C. graminicola in maize that are spread across the regions of Brazil. In general, the strains tended to show the same reaction as that obtained in the first F L150, L151, L152, L153, L154, L155, L156, L157, L158, L159, L160, L161, L162, L163, L164, L165, L166, L167, L168, L169 G L170, L171, L172, L173, L174, L175, L176, L177, L178, L179, L180, L181, L182, L183, L184, L185, L186, L187, L188, L189, L190, L191, L192, L193, L194, L195, L196, L197, L198, L199, L200 H L201, L202, L203, L204, L205, L206, L207, L208, L209, L210, L211, L212, L213, L214, L215, L216, L217, L218, L219, L220, L221, L222, L223, L224, L225, L226, L227, L228, L229, L230, L231, L232, L233, The evaluation method adopted in the present study was efficient to classify the lines to form different resistance categories to anthracnose stalk rot, as done in many reports (CARSON & HOOKER, 1981;BADU-APRAKU et al, 1987;TOMAN & WHITE, 1993;COTA et al, 2010;MATIELLO et al, 2012;COSTA at al., 2014).…”
Section: Resultsmentioning
confidence: 69%
“…Resistant cultivars carry genes with resistance to stalk rot infection, which are transferred via a quantitative inheritance mode, with the predominance of an additive genetic effect (CARSON & HOOKER, 1981;BADU-APRAKU et al, 1987;TOMAN & WHITE, 1993;BERGSTROM & NICHOLSON, 1999;PALAVERSIC et al, 2009;MATIELLO et al, 2012). Maize genotypes showing different levels of anthracnose stalk rot resistance have been described in germplasm banks; examples of such genotypes are the following: MP305, DE811ASR (JUNG et al, 1994, BROGLIE et al, 2006FREY et al, 2011);DW1035 (TOMAM & WHITE, 1993; A556, A638, Oh43, R177 (CARSON & HOOKER, 1981); RD6502 (BADU-APRAKU et al, 1987);Bc19064 (PALAVERSIC et al, 2009);CML52 (CHUNG et al, 2011);Das2, Das64 (MATIELLO et al, 2012); H8664 (MATIELLO et al, 2013); 2B710 (GARDINGO, 2008;COSTA et al, 2010b;COTA et al, 2010;CARVALHO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%